Liability of limited liability companies through the single economic doctrine - Sembiring, Raminda Unelly Maret; Murwadji, Tarsisius; Suryanti, Nyulistiowati (Edelweiss Applied Science and Technology, 2025)
The existence of business groups is currently growing rapidly because they can serve as a solution for companies to strengthen their defenses in facing various challenges of free trade. The Single Economic Entity Doctrine theory views the relationship between parent and subsidiary companies, where the subsidiary does not have independence in determining the company’s policy, as a single economic entity. The degree of independence of a subsidiary can be assessed through various factors, including the parent company’s control over the subsidiary’s board of directors, the profits enjoyed by the parent company from the subsidiary, and the subsidiary’s compliance with policies set by the parent company, such as those related to marketing and investment. The application of the Single Economic Entity Doctrine in Indonesian competition law has sparked considerable controversy, mainly because Indonesia does not yet recognize this doctrine. Additionally, Law No. 40 of 2007 on Limited Liability Companies (UUPT) adheres solely to the principle of independent legal entities and does not mention business groups, nor does it incorporate extraterritoriality.